Development of the Distribution of Household Income in Austria - Gudrun Biffl (Austrian Institute of Economic Research (WIFO), 2007)
This paper puts emphasis on the earnings development at the lower end of the earnings distribution and its development over time. The main objective is to provide more insight into the mechanism of impoverishment and marginalisation of various groups of people as well as the dynamics.
Keywords: 330; Einkommensverteilung; Haushaltseinkommen; Österreich